China’s policy for the marine engineering equipment industry and potential challenges: An appraisal of the new developments under the 14th five-year plans - Zhang, Hu; Wang, Qiuwen; Huang, Jiabei (Frontiers in Marine Science, 2022)
The Five-Year Plans are China’s most important macroeconomic and social management tool, setting goals and directions for the national economic and social development vision. To date, China has implemented 13 periods of Five-Year Plans. On March 12, 2021, the Chinese government adopted its 14th Five-Year Plan, which requires breakthrough the key core technologies of marine engineering and cultivating and expanding the marine engineering equipment industry. This research conducts a policy analysis to comprehensively examine the development plans for the marine engineering equipment industry in these 14th Five-Year Plans issued by China’s central level and local level governments. By summarizing and analyzing these policies pertaining to the marine engineering equipment industry, it aims to show a holistic picture for the new policy developments in China’s new five-year period. This paper also highlights the challenges and pressures that might be faced by the Chinese authorities in the policy implementation stage.